Dialkylcarbamoyl chloride‐coated versus alginate dressings after pilonidal sinus excision: a randomized clinical trial (SORKYSA study). Issue 2 (4th February 2020) - Romain, B.; Mielcarek, M.; Delhorme, J. B.; Meyer, N.; Brigand, C.; Rohr, S.; ,
Abstract : Background: Disease of the pilonidal sinus is a common condition that affects mainly young adults. Options for management include excision of the sinus tracts, leaving the wound open to heal by secondary intention. The aim of this study was to compare wound healing with dialkylcarbamoyl chloride (DACC)‐coated dressings versus alginate dressings. Methods: This multicentre trial randomized consecutive patients undergoing surgery for pilonidal disease to postoperative wound care with either DACC‐coated or alginate dressings. The primary outcome was the proportion of wounds healed after 75 days. Secondary outcomes were the local status of wounds during the healing process, the quality assessment of the dressings by the patient, and the time needed to return to usual activities. Results: A total of 246 patients were included: 120 in the DACC‐coated group and 126 in the alginate group. In per‐protocol analysis, there were significantly more patients with completely healed wounds after 75 days in the DACC group than in the alginate group: 78 of 103 (75·7 per cent) versus 58 of 97 (60 per cent) respectively (odds ratio 2·55, 95 per cent c.i. 1·12 to 5·92; P  = 0·023). During follow‐up, wounds with alginate dressings had more fibrin than those with DACC‐coated dressings, but the difference was not significant ( P  = 0·079). There was no difference between the two arms in patients' assessment of the dressings. Conclusion: The number of wounds completely healed at 75 days was significantly higher for DACC‐coated compared with alginate dressings. However, the preplanned, clinically significant improvement in healing of 20 per cent was not reached. Registration number: NCT02011802 ( https://clinicaltrials.gov/ ). Abstract : This multicentre RCT compared the efficacy of dialkylcarbamoyl chloride (DACC)‐coated dressings with alginate dressings for wound healing after pilonidal sinus excision. In per‐protocol analysis, significantly more patients had completely healed wounds at 75 days in the DACC group than in the alginate group: 78 of 103 (75·7 per cent) versus 58 of 97 (60 per cent) respectively (odds ratio 2·55, 95 per cent c.i. 1·12 to 5·92; P  = 0·023). No clinically important difference Abstract : Antecedentes: El sinus pilonidal es una afección común que afecta principalmente a adultos jóvenes. Las opciones de tratamiento incluyen la escisión de los trayectos del sinus, dejando la herida abierta para cicatrizar por segunda intención. El objetivo de este estudio fue comparar la cicatrización de heridas con apósitos recubiertos con cloruro de diaquilcarbamoilo ( dialkylcarbamoyl chloride, DACC) en comparación con apósitos de alginato. Métodos: En este ensayo multicéntrico se asignó al azar a pacientes consecutivos sometidos a cirugía por sinus pilonidal a uno de los dos brazos: cuidado postoperatorio de heridas con apósitos recubiertos con DACC o con alginato. El criterio de valoración principal fue la proporción de heridas curadas después de 75 días. Los criterios de valoración secundarios fueron el estado local de las heridas durante el proceso de curación, la evaluación de la calidad de los apósitos por parte del paciente y el tiempo necesario para volver a la actividad profesional. Resultados: Se incluyeron un total de 246 pacientes: 120 en el grupo de apósitos recubiertos de DACC y 126 en el grupo de alginato. En el análisis por protocolo, hubo significativamente más pacientes con heridas completamente curadas después de 75 días en el grupo DACC que en el grupo de alginato: 78 de 103 (75, 7%) y 58 de 97 (59, 7%) respectivamente (razón de oportunidades, odds ratio, OR = 2, 55; (1, 12; 5, 92); P = 0, 02)). Durante el seguimiento, las heridas recubiertas con apósitos de alginato tenían más fibrina que las recubiertos con DACC, pero la diferencia no fue significativa ( P = 0, 08). No hubo diferencias entre los dos brazos en la evaluación realizada por los pacientes de los apósitos. Conclusión: El número de heridas completamente curadas a los 75 días fue significativamente mayor con los apósitos recubiertos con DACC en comparación con los apósitos de alginato. Sin embargo, no se alcanzó la mejoría clínicamente significativa preestablecida de una curación del 20%.